The prevalence of peri‐implant diseases for two‐piece implants with an internal tube‐in‐tube connection: a cross‐sectional analysis of 512 implants. Issue 1 (14th July 2015) - Schwarz, Frank; Becker, Kathrin; Sahm, Narja; Horstkemper, Thomas; Rousi, Khalifa; Becker, Jürgen
Abstract: Objectives: To assess the prevalence of peri‐implant health or disease for a two‐piece implant system with a tube‐in‐tube internal connection on the short‐, medium‐ and long term. Material and methods: For this cross‐sectional analysis, 238 patients with a total of n = 512 implants were screened in six private practices and one university clinic in Germany. Peri‐implant health and disease was assessed according to strict case definitions. Binary logistic regression was used to assess the correlation with systemic factors. Results: After a median function time of 23 months, the prevalence of peri‐implant mucositis and peri‐implantitis amounted to 41.6% and 13.9%, corresponding to 35.6% and 7.6% at the implant level, respectively. Factors plaque (odds ratio [OR], 8.415) and gender "male" (OR, 2.003) were significantly correlated with the event peri‐implant mucositis. The event peri‐implantitis was significantly correlated with plaque (OR, 9.250) and smoking (OR, 2.679). Conclusion: The prevalence of peri‐implant diseases was correlated with patient‐specific factors.